The Role of Accompaniment in Reducing Anxiety of Pregnant Women Ahead of Childbirth - Ellyzabeth Sukmawati (PT Inovasi Pratama Internasional, 2026)
Anxiety during pregnancy, particularly approaching childbirth, is a common psychological condition that may negatively affect maternal well-being and fetal outcomes. Elevated anxiety has been associated with adverse consequences such as prolonged labor, increased operative delivery, and higher risk of preterm birth. Therefore, an adequate support system—including partners, family members, and healthcare providers—plays a crucial role in helping pregnant women cope with emotional distress and enhancing childbirth readiness. This study aims to examine the role of support systems in reducing anxiety among pregnant women through a systematic review approach. Literature was searched across major databases, including MEDLINE, Embase, and Google Scholar, using keywords related to pregnancy anxiety, social support, partner support, and psychological interventions. Eligible studies were original research articles published in English or Indonesian between 2000 and 2023, available in full text. Findings from the included studies were synthesized narratively. The review indicates that partner (husband) support is consistently associated with lower anxiety levels, improved maternal confidence, and better preparedness for childbirth. Family support, counseling, and educational interventions also contribute to increased self-efficacy and adherence to antenatal care. In conclusion, a strong and coordinated support system is essential in mitigating anxiety during pregnancy and promoting positive maternal outcomes.